Analisis Investasi dalam Piutang dan Pengaruhnya Terhadap Rentabilitas Pada PT Bank Pembiayaan Rakyat Syariah Lantabur Jombang - Wahyuni, Dwi; Ni'mah, Ni'mah (Business and Accounting Education Journal, 2021)
This study aims to examine the effect of the investment variable in accounts receivable on profitability at PT. BPRS LantaburJombang. This researcher used quantitative descriptive methods by analyzing the effect of investment in receivables on profitability at PT. BPRS LantaburJombang 2017-2020. Methods of data collection using documentation and interviews. The statistical analysis model used is the simple linear regression model statistical test and the F-test. Based on the analysis of the results above, it shows that the effect of investment in accounts receivable on profitability is very small.